2020
DOI: 10.1088/1361-6595/ab6074
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for solving the Boltzmann equation of electrons in weakly ionized plasma

Abstract: A novel direct numerical method to calculate the electron velocity distribution function (EVDF) in hydrodynamic equilibrium under a uniform DC electric field is presented. In the present method, an artificial feedforward neural network learns the EVDF governed by both the Boltzmann equation and boundary conditions. The present method dost not require the expansion of the EVDF in the Legendre polynomials and the discretization of both the EVDF and the Boltzmann equation. As a benchmark, the EVDF in Reid's ramp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…33,34 Automatic differentiation is again exploited to obtain desired partial derivatives with respect to the input variables. 35 Early work in LTP has been proposed by Kawaguchi et al 50 who have considered a PINN solution to the stationary Boltzmann equation subject to ionization and electron attachment processes. An MLP has been trained to predict the electron velocity distribution function (EVDF) following an exponential ansatz.…”
Section: Physics-informed Machine Learningmentioning
confidence: 99%
“…33,34 Automatic differentiation is again exploited to obtain desired partial derivatives with respect to the input variables. 35 Early work in LTP has been proposed by Kawaguchi et al 50 who have considered a PINN solution to the stationary Boltzmann equation subject to ionization and electron attachment processes. An MLP has been trained to predict the electron velocity distribution function (EVDF) following an exponential ansatz.…”
Section: Physics-informed Machine Learningmentioning
confidence: 99%
“…where B is the magnetic field. Finally, the electron density under the magnetic field can be calculated by Equation ( 9) in the experiment, the results measured by the probe will also be corrected by Equation (9) to train the machine learning model.…”
Section: Correction Of the Probementioning
confidence: 99%
“…Considering that under the influence of the magnetic field, the accuracy and parameter range of the probe diagnostic are greatly limited, and machine learning technology can break through this limitation by deeply mining information and summarizing physical laws. Recently, there have been some studies using machine learning to improve probe diagnostic methods, [ 9 ] and some studies have demonstrated the feasibility of applying machine learning technology in principle. [ 10 ] In addition, the machine learning algorithm is applied to plasma parameter diagnosis to improve the precision and measurement range of probe diagnostic.…”
Section: Introductionmentioning
confidence: 99%
“…Kawaguchi et al. [40] used an artificial feed‐forward neural network to solve Boltzmann's equation for an electron velocity distribution function. Mesbah et al.…”
Section: Introductionmentioning
confidence: 99%